Dual Role of Mesenchymal Stem Cells Allows for Microvascularized Bone Tissue‐Like Environments in PEG Hydrogels. Issue 4 (22nd December 2015) - Blache, Ulrich; Metzger, Stéphanie; Vallmajo‐Martin, Queralt; Martin, Ivan; Djonov, Valentin; Ehrbar, Martin
Abstract : In vitro engineered tissues which recapitulate functional and morphological properties of bone marrow and bone tissue will be desirable to study bone regeneration under fully controlled conditions. Among the key players in the initial phase of bone regeneration are mesenchymal stem cells (MSCs) and endothelial cells (ECs) that are in close contact in many tissues. Additionally, the generation of tissue constructs for in vivo transplantations has included the use of ECs since insufficient vascularization is one of the bottlenecks in (bone) tissue engineering. Here, 3D cocultures of human bone marrow derived MSCs (hBM‐MSCs) and human umbilical vein endothelial cells (HUVECs) in synthetic biomimetic poly(ethylene glycol) (PEG)‐based matrices are directed toward vascularized bone mimicking tissue constructs. In this environment, bone morphogenetic protein‐2 (BMP‐2) or fibroblast growth factor‐2 (FGF‐2) promotes the formation of vascular networks. However, while osteogenic differentiation is achieved with BMP‐2, the treatment with FGF‐2 suppressed osteogenic differentiation. Thus, this study shows that cocultures of hBM‐MSCs and HUVECs in biological inert PEG matrices can be directed toward bone and bone marrow‐like 3D tissue constructs. Abstract : 3D cocultures of human mesenchymal stem cells (MSCs) and human endothelial cells (ECs) can be directed toward vascularized bone mimicking tissue constructs in synthetic biomimetic poly(ethylene glycol) (PEG)‐based matrices. In this microenvironment, MSCs can fulfill two tasks: they a) support the formation of microvascular structures by endothelial cells and b) can be simultaneously osteogenic differentiated.